Replication data for: Visualization of finite-time separation in multiphase flow - Heinemann, Moritz; Potyka, Johanna; Schulte, Kathrin; Sadlo, Filip; Ertl, Thomas (Universität Stuttgart, 2024)
Collision of a droplet chain of a 50% water-glycerol solution colliding with a continuous jet of silicon oil M5, which is a combination of immiscible liquids. The collision process leads to the separation of compound droplets, i.e., the droplets are encapsulated by the jet's liquid. The Cartesian simulation grid originally had a size of 2048 x 1024 x 256 cells covering a domain of 0.704 cm x 0.352 cm x 0.088 cm. The dataset consists of 157 output time steps covering a time span of 1.872 ms. Only half of the jet and droplets were simulated with a mirror boundary condition at the z=0 plane. We reduced the size of the here published data by converting all double-precision floating-point values to single-precision and cropping the grid to regions containing fluid. This results in a grid size of 2048 x 768 x 128 cells. Finally, the data is stored in the VTK XML file format utilizing the built-in zlib compression. The dataset is stored as a rectilinear grid and contains the following fields: f3-function[-]: volume fractions of the f3-field ("droplets") vof-function[-]: volume fractions of the f-field ("jet") n_c_3ph[1]: PLIC normals for the f-field in three-phase cells velocity[cm/s]: velocity-field In addition, two spatially downsampled variants of the dataset are attached. The 'ds1' directory is a downsampled variant where every eight cells were averaged to a single cell. The 'ds2' directory is downsampled the same way using the 'ds1' data. This simulation is a variant of the simulation initially presented in [1] using a slightly larger domain and was run on the Hawk supercomputer specifically for our paper. The specific method used in the simulation is presented in [2] and is implemented in FS3D [3]. References: [1] Potyka et al.: Towards DNS of Droplet-Jet Collisions of Immiscible Liquids with FS3D, "https://doi.org/10.1007/978-3-031-46870-4_14" https://doi.org/10.1007/978-3-031-46870-4_14. [2] Potyka and Schulte: A volume of fluid method for three dimensional direct numerical simulations of immiscible droplet collisions, "https://doi.org/10.1016/j.ijmultiphaseflow.2023.104654" https://doi.org/10.1016/j.ijmultiphaseflow.2023.104654. [3] Eisenschmidt et al., Direct Numerical Simulations for Multiphase Flows: An Overview of the Multiphase Code FS3D, "https://doi.org/10.1016/j.amc.2015.05.095" https://doi.org/10.1016/j.amc.2015.05.095.
Updated: 2024-11-12
DFG: 84292822
Keywords: Forschungsdaten